Pengaruh Lingkungan Kerja, Beban Kerja, Stress Kerja Terhadap Kepuasan Kerja Pegawai Pada Kantor Ksop Kelas Iv Bakauheni - Hendry Putralau; Lukmanul Hakim (Hikamatzu | Journal of Multidisciplinary, 2026)
This study aims to analyze the effect of work environment, workload, and work stress on employee job satisfaction at the Kantor Kesyahbandaran dan Otoritas Pelabuhan (KSOP) Class IV Bakauheni. A quantitative approach was employed using a survey method with data collected through questionnaires distributed to all employees as a saturated sample, totaling 47 respondents. The independent variables include work environment, workload, and work stress, while the dependent variable is job satisfaction. Data analysis was conducted using multiple linear regression to examine both partial and simultaneous effects of independent variables on job satisfaction. The results indicate that the work environment has a positive and significant effect on job satisfaction, where a conducive, safe, and well-equipped environment enhances employee motivation and comfort. Workload also significantly affects satisfaction, with proportional workloads fostering efficiency, whereas excessive workload generates stress and fatigue. Work stress was found to negatively influence job satisfaction, particularly when job demands exceed individual capacity. Simultaneously, these three variables contribute significantly to shaping employee job satisfaction